Pengembangan Media Pembelajaran Tanaman Obat Tradisional Menggunakan Metode Multimedia Development Life Cycle - Muhammad Fauzan Yasykur; Neo Mauizan Ali Fitrah; Nanda Ega Wijaya Saputra (STMIK Palangkaraya, 2024)
Maintaining health is a crucial aspect of human life, and one traditional method to boost the immune system is through the use of medicinal plants. The practice of using medicinal plants has been passed down through generations, but in the present era, there is a decline in interest, particularly among the younger generation due to a lack of knowledge about the benefits of medicinal plants. This research aims to develop an interactive learning media introducing traditional medicinal plants, named